14 Years of PID Services at the German National Library of Science and Technology (TIB): Connected Frameworks, Research Data and Lessons Learned from a National Research Library Perspective. (17th July 2017) - Kraft, Angelina; Dreyer, Britta; Löwe, Peter; Ziedorn, Frauke
In an ideal research world, any scientific content should be citable and the coherent content, as well as the citation itself, should be persistent. However, today's scientists do not only produce traditional research papers – they produce comprehensive digital resources and collections. TIB's mission is to develop a supportive framework for a sustainable access to such digital content – focusing on areas of engineering as well as architecture, chemistry, information technology, mathematics and physics. The term digital content comprises all digitally available resources such as audiovisual media, databases, texts, images, spreadsheets, digital lab journals, multimedia, 3D objects, statistics and software code. In executing this mission, TIB provides services for the management of digital content during ongoing and for finished research. This includes: a technical and administrative infrastructure for indexing, cataloguing, DOI registration and licensing for text and digital objects, namely the TIB DOI registration which is active since 2005, the administration of the ORCID DE consortium, an institutional network fostering the adoption of ORCID across academic institutions in Germany, training and consultancy for data management, complemented with a digital repository for the deposition and provision of accessible, traceable and citable research data (RADAR), a Research and Development Department where innovative projects focus on the visualization and the sustainable access to digital information, and the development of a supportive framework within the German research data community which accompanies the life cycle of scientific knowledge generation and transfer. Its goal is to harmonize (meta)data display and exchange primarily on a national level (LEIBNIZ DATA project).